Barbados : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that since the early 1990s, Barbados has been experiencing steady economic growth founded on prudent economic management and generally favorable external conditions. Economic policy has incorporated fiscal and wage restraint, consistent with the maintenance of the long-standing exchange parity with the U.S. dollar. In 1998, real GDP growth picked up, based on strong performances in the tourism and construction sectors, although a drought led to a decline in sugar output.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet